Experimental Results on Active Control of Buzz Saw Noise Tones of Aero Engines - Maier, R.; Zillmann, J.; Enghardt, L.; Genoulaz, N. (International journal of aeroacoustics, 2007)
The potential of active noise control (ANC) to reduce buzz saw noise tones has been evaluated in the framework of the European funded project SILENCE(R). A scaled fan with 0.85m diameter from Rolls-Royce was used as test vehicle. Testing took place at a new facility at Anecom Aerotest located near Berlin. The paper deals with the results obtained by applying a modal control algorithm [1], [2] developed by EADS-CRC. With this algorithm, control was restricted to single azimuthal modes, whereby the mode number is equal to the engine order due to the special properties of buzz saw noise tones. The algorithm and its realtime implementation are presented in some detail. Furthermore, main advantages as well as drawbacks of the control concept are discussed. A ring of 30 loudspeakers mounted at the inner wall of the inlet duct was used as secondary acoustic sources and a single ring with 30 microphones made from electret film material has been used as error sensors. The film microphones were directly glued on the inlet duct. The sound field with and without active control has been measured in the duct by two microphone rings upstream of the error sensor ring and in the far-field by a circular microphone array in a single plane. The far-field measurements have been evaluated by SNECMA. The induct measurements were used by DLR to perform a mode decomposition of the sound field. The control of up to 3 buzz saw noise tones has been successfully demonstrated simultaneously.